Integration of Metabolomics and Transcriptomics for Investigating the Tolerance of Foxtail Millet (Setaria italica) to Atrazine Stress - Sun, Lifang; Liu, Libin; Wang, Yuting; Feng, Yanfei; Yang, Wei; Wang, Di; Gao, Shuren; Miao, Xingfen; Sun, Wentao (Frontiers in Plant Science, 2022)
Foxtail millet (Setaria italica) is a monotypic species widely planted in China. However, residual atrazine, a commonly used maize herbicide, in soil, is a major abiotic stress to millet. Here, we investigated atrazine tolerance in millet based on the field experiments, then obtained an atrazine-resistant variety (GA2) and an atrazine-sensitive variety (LG31). To examine the effects of atrazine on genes and metabolites in millet plants, we compared the transcriptomic and metabolomic profiles between GA2 and LG31 seedling leaves. The results showed that 2208 differentially expressed genes (DEGs; 501 upregulated, 1707 downregulated) and 192 differentially expressed metabolites (DEMs; 82 upregulated, 110 downregulate) were identified in atrazine-treated GA2, while in atrazine-treated LG31, 1773 DEGs (761 upregulated, 1012 downregulated) and 215 DEMs (95 upregulated, 120 downregulated) were identified. The bioinformatics analysis of DEGs and DEMs showed that many biosynthetic metabolism pathways were significantly enriched in GA2 and LG31, such as glutathione metabolism (oxiglutatione, γ-glutamylcysteine; GSTU6, GSTU1, GSTF1), amino acid biosynthesis (L-cysteine, N-acetyl-L-glutamic acid; ArgB, GS, hisC, POX1), and phenylpropanoid biosynthesis (trans-5-o-(4-coumaroyl) shikimate; HST, C3’H). Meanwhile, the co-expression analysis indicated that GA2 plants had enhanced atrazine tolerance owing to improved glutathione metabolism and proline biosynthesis, and the enrichment of scopoletin may help LG31 plants resist atrazine stress. Herein, we screened an atrazine-resistant millet variety and generated valuable information that may deepen our understanding of the complex molecular mechanism underlying the response to atrazine stress in millet.